Effect of nutritional therapy in Emery–Dreifuss muscular dystrophy: a case report - Valoriani, Filippo; Pinelli, Giovanni; Gabriele, Silvia; Menozzi, Renata (Frontiers in Nutrition, 2024)
Emery–Dreifuss muscular dystrophy (EDMD) is a rare, inherited human disease. Similar to other neuromuscular dystrophies, EDMD is clinically characterized by muscle atrophy and weakness, multi-joint contractures with spine rigidity, and cardiomyopathy. Over time, muscular weakness can lead to dysphagia and a severe lowering of body mass index (BMI), worsening the prognosis. We present the case of a young male patient affected by EDMD, admitted to the hospital for pneumothorax in a severe state of undernourishment. The patient was treated with total parenteral nutrition (TPN) with Smofkabiven®, supplemented with micronutrients (vitamins and trace elements), and with minimal enteral nutrition through food. Within a year, the patient gained 8.5 kg and kept his body weight stable for the 6 years of the follow-up. In this study, we show that TPN ensures the nutritional requirements of EDMD patients in a safe and well-tolerated manner, allowing a considerable and stable improvement in nutritional status, which has a positive impact on the disease itself and the patients’ quality of life.